2006
DOI: 10.1007/s11575-006-0042-5
|View full text |Cite
|
Sign up to set email alerts
|

Process perspectives in international business research in CEE

Abstract: Abstract• Internationalisation processes have been a core interest of international business research since the seminal contribution by Johanson/Vahlne (1977).• The unique context of economic transition in CEE directs the attention to dynamic aspects of these processes, and to the interaction with changing environmental conditions.• This introductory paper reviews the contributions of recent CEE research, and this special issue in particular, to advancing our understanding of internationalisation processes. Ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(83 citation statements)
references
References 46 publications
1
77
0
5
Order By: Relevance
“…This work can build from the observation that it is at points of inflection of institutional evolution in an economy that frictions between a firm's strategies and their degree of institutional alignment become most pronounced. This interaction between institutional change and organizational change is particularly well-suited to examination in a CEE context because of the continued temporal dynamics of these processes, and the opportunities for comparative cross-national research in the CEE, where many nations have undergone different forms of transition (Meyer and Peng, 2005;Meyer and Gelbuda, 2006). Some management scholars synthesize, or selectively combine, the two strands of closely related theoretical work (Peng, 2003;Peng et al, 2005).…”
Section: The Two Institutional Perspectives and Research In Cee Countmentioning
confidence: 99%
See 1 more Smart Citation
“…This work can build from the observation that it is at points of inflection of institutional evolution in an economy that frictions between a firm's strategies and their degree of institutional alignment become most pronounced. This interaction between institutional change and organizational change is particularly well-suited to examination in a CEE context because of the continued temporal dynamics of these processes, and the opportunities for comparative cross-national research in the CEE, where many nations have undergone different forms of transition (Meyer and Peng, 2005;Meyer and Gelbuda, 2006). Some management scholars synthesize, or selectively combine, the two strands of closely related theoretical work (Peng, 2003;Peng et al, 2005).…”
Section: The Two Institutional Perspectives and Research In Cee Countmentioning
confidence: 99%
“…Moreover, cognitive barriers inhibited managers' understanding of how best to operate under the conditions of a volatile market economy (Meyer and Gelbuda, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…But as Johanson and Vahlne have repeatedly observed (1990,2006), these empirical patterns do not constitute the internationalization process model; rather, they are the empirical phenomena (i.e., internationalization patterns) that the model seeks to explain (see also Hadjikhani 1997;Meyer and Gelbuda 2006;Petersen and Pedersen 1997). Johanson and Vahlne observed in 2006 that the result of this mistaken identity has been that the core mechanism in the model-the interplay between learning and commitment processes-has not been empirically tested or further developed conceptually.…”
Section: Misunderstanding Nomentioning
confidence: 99%
“…Andersen & Kheam, 1998;Sapienza, Autio, George & Zahra, 2006). Further, to make it possible for us to address the complexity of factors and processes interacting over time, several scholars have argued that internationalisation should be examined holistically with the help of longitudinal case studies (Coviello & Jones, 2004;Liesch, Welch, Welch, McGaughey, Petersen & Lamb, 2002;Meyer & Gelbuda, 2006). Indeed, it seems that earlier research has identified most of the core aspects relating to the internationalisation of the firm.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it seems that earlier research has identified most of the core aspects relating to the internationalisation of the firm. However, as recent studies have emphasized (Coviello & Jones, 2004;Liesch et al, 2003;Meyer & Gelbuda, 2006), more attention should be paid to the relations between these factors and longitudinal research that captures the dynamic and complex nature of internationalisation. The purpose of the present study is to contribute to this endeavour.…”
Section: Introductionmentioning
confidence: 99%